The enigma of the suicide bomber a psychoanalytic essay - De Masi, Franco (Karnac Books, 2011)
"Why does someone resolve to take his own life in order to murder other people? What is the state of mind which allows him to commit such a monstrous act? This book explores the mental state that compels certain individuals to perform murderous, suicidal acts and emphasizes that, whereas a suicidal terrorist attack can be described as a crime against humanity, its protagonists cannot necessarily be classified as criminal or insane. There is no such a thing as a "typical" suicide terrorist - each attacker differs in age, sex, family status, culture, and even religion. Indeed, the common elements in suicide terrorism should perhaps be sought not so much in the individuals concerned as in the dynamics rooted in their group, family history or country. It may be extreme situations experienced by the group situations that are either objectively extreme or perceived as such that give rise to paradoxical behaviour at individual level. Psychoanalysis is well placed to consider this terrain [if you can think of a better word than "terrain" that would be OK]. Freud, after all, soon disabused his reader of the belief that the less palatable aspects of psychic life were the exclusive preserve of some aberrant sub-category of people." --Publisher's website